Adenosine deaminase and Guanase deaminase activities in serum of patients with rheumatoid arthritis - Önal, Süleyman; Erel, Özcan; Çolak, Mesut; Bulut, Vedat (My University, 2012)
We investigated purin and primidin salvage pathways in rheumatoid arthritis (RA). For the aim, Adenosine deaminase (AD) and Guanosine deaminase (GD) activities in serum of patients with di!erent manifestations of the disease (n=32) were investigated and compared with the control group of healthy individuals (n=52). RA cases were classified with respect to their clinics and treatment. The ADA activities were significantly higher (p<0.01) in patients with RA than in control although GD activity levels were found to be lower (p<0.01). When compared their AD and GD levels amongst the classified RA groups, there was no di!erence in AD levels amongst cases. In conclusion, increased serum AD activities in patients with RA may be dependent on and reflect the increase in phagocytic activity of macrophages and maturation of T-lymphocytes. The results indicated that plasma AD and GA activity can be used for the diagnosis of RA disease to support clinical findings and as an index for disease.
Keywords: Adenosine deaminase; Guanosine deaminase; Inflammation; Rheumatoid arthritis